Awareness, Treatment, and Control of Hypertension among the Adult Population in Burkina Faso: Evidence from a Nationwide Population-Based Survey - Kadari Cissé; Seni Kouanda; Yves Coppieters’t Wallant; Fati Kirakoya-Samadoulougou (International Journal of Hypertension)
Background. Hypertension is the leading cause of cardiovascular disease, particularly in low- and middle-income countries. Improved awareness of hypertension status can significantly increase early treatment, thereby reducing cardiovascular complications and premature death. This study aimed to report the prevalence of the awareness, treatment, and control of hypertension among the adult population in Burkina Faso. Method. We performed a secondary analysis of the first national population-based survey on common risk factors of noncommunicable diseases in Burkina Faso. It was a national representative cross-sectional survey among adults aged 25–64 years. Awareness of hypertension was defined by blood pressure ≥140/90 mmHg or a prior diagnosis by a health worker or the use of any antihypertensive drugs. A modified Poisson regression model using a generalized estimating equation was used to identify factors associated with awareness of hypertension. Result. A total of 4628 people with valid blood pressure measurements were considered. Of them, 828 had hypertension. Among people with hypertension, the prevalence of awareness was 17.5% (95% CI: 14.4%–21.1%), and 47.3% (95% CI: 37.6%–57.3%) of them had taken antihypertensive medications for their hypertension. One-third (35.5% (95% CI: 23.3%–49.9%)) of those who took medications had controlled hypertension. The prevalence of awareness was significantly higher among women (21.1% (95% CI: 16.4%–26.7%)) compared with men (13.8% (95% CI: 10.4%–17.9%)) (p=0.019). The prevalence of awareness increased with increasing age and education level. Nearly one-third (29.3% (95% CI: 25.3%–33.6%)) of people with hypertension needed antihypertensive drug treatment. Conclusion. There was a poor level of awareness, treatment, and control of hypertension among adults in Burkina Faso. Effective control strategies to increase the screening of hypertension in primary care and at the community level are necessary in Burkina Faso.